Mission Book Game: Enhancing Fifth-Grade Students’ Learning Motivation on Thematic Learning - Dewa Ayu Candra Dwi Evayani; I Nyoman Jampel; I Wayan Widiana (Universitas Pendidikan Ganesha, 2021)
The lack of use of learning media in the learning process causes students to find it difficult to understand the material. This study aims to produce learning media that can increase students' motivation and activeness in the learning process. Media development in this study is guided by the ADDIE model procedure which consists of several stages, namely analysis (analyze), design (design), development (development), implementation, and evaluation (evaluate). The subject in this development research is the mission book game media to increase the learning motivation of fifth-grade students while the object in this research is the validity and effectiveness of the mission book game media developed. This development research method is a qualitative and quantitative analysis method. The data collection used is a questionnaire method with data collection instruments in the form of a rating scale by giving an assessment instrument to 4 experts, namely, 2 material experts, 2 media experts, 2 practitioner responses, and 12 students. The data were analyzed by testing the validity and reliability test of the mission book game media based on data from experts, practitioners, and students' responses. The data obtained is calculated using the mean formula to determine the average validity of the media. The average validity score of the mission book media game in terms of material experts is 4.8 with very valid criteria, in terms of media experts it is 4.4 with very valid criteria, in terms of practitioner responses it is 4.7 with very valid criteria and in terms of student response of 4.9 with very valid criteria. The motivational data analysis technique used is descriptive quantitative statistical data analysis techniques in the form of prerequisite tests and t-tests. The results of the hypothesis test showed a significance value of 0.033 which means 0.033 <0.05, so it can be concluded that there is an effect of the.